FIELD GRASS SILAGE WITH THE ADDITION OF COLI FRUIT FIBER QUESTION AS RUMINANT ANIMAL FEED - Saiklela, Desy Megi; Sangadji, Insun; Patty, Christian Willem (Universitas Pattimura, 2023)
This research aims to find out what % of coli fruit fiber juice is used to produce good quality silage, and to find out the physical quality of field grass silage with the addition of coli fruit fiber juice. The materials used in this research were field grass and coli fruit fiber juice brought from Moa Island, Southwest Maluku Regency. This research will be carried out for 2 months (October-November, 2022) at the Faculty of Agriculture, Animal Husbandry Department, Pattimura University, Ambon. The harvested silage will be subject to observation and/or physical analysis of field grass silage at the Animal Nutrition and Forage Laboratory, Pattimura University, Ambon. The variables observed were color, aroma, texture, pH and the presence or absence of mold in the silage. The physical quality was tested by the 5 students selected as panelists using the questionnaire provided.